Effect of Liquid Fertilizer Based on Local Microorganisms on Soil Fertility and Maize Production - Magdalena Sunarty Pareira; Venti Jatsiyah (West Science Nature and Technology, 2024)
The use of liquid fertilizers based on local microorganisms offers a sustainable solution for enhancing soil fertility and maize production. This study provides a comprehensive literature review of 11 Scopus-indexed articles to examine the effects of these fertilizers on soil health and crop yield. The findings reveal significant improvements in soil organic matter, microbial diversity, and nutrient availability, alongside enhanced maize growth parameters such as germination, biomass accumulation, and grain yield. Despite the variability in results due to environmental factors and application methods, these fertilizers demonstrate the potential to reduce dependency on synthetic inputs and align with sustainable agricultural practices. Challenges related to scalability, economic feasibility, and long-term impacts necessitate further research to optimize their implementation in diverse agricultural settings.